The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/andr.12875
|View full text |Cite
|
Sign up to set email alerts
|

Icariin modulates eNOS activity via effect on post‐translational protein‐protein interactions to improve erectile function of spontaneously hypertensive rats

Abstract: Background Type 5 phosphodiesterase inhibitor (PDE5I) has become the first‐line treatment for erectile dysfunction (ED). However, its effective rate for hypertension ED is only 60%‐70%. How to improve the efficacy of ED treatment is the focus of current research. Objective To explore whether icariin can improve the erectile function of spontaneously hypertensive rats (SHR) by affecting post‐translational protein‐protein interactions to regulate endothelial nitric oxide synthetase (eNOS) activity. Method Twelve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 36 publications
3
11
0
Order By: Relevance
“…ARB can promote the release of nitric oxide and accelerate the effect of acetylcholine on endothelium-dependent vasodilation [ 69 ]. These compounds can reverse endothelial dysfunction spontaneously hypertensive rats [ 70 ] and ameliorate FMD in patients with hypertension. CCB not only effectively reduces blood pressure but also increases the production of endothelial nitric oxide synthase, thereby improving nitric oxide bioavailability and endothelial function [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…ARB can promote the release of nitric oxide and accelerate the effect of acetylcholine on endothelium-dependent vasodilation [ 69 ]. These compounds can reverse endothelial dysfunction spontaneously hypertensive rats [ 70 ] and ameliorate FMD in patients with hypertension. CCB not only effectively reduces blood pressure but also increases the production of endothelial nitric oxide synthase, thereby improving nitric oxide bioavailability and endothelial function [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated MAP-like SHR induced hypertension could induce ED with the decreased the level of maximum penile intracavernous pressure/MAP (ICPmax/MAP) by the decreased eNOS and HSP90 interaction, 34 and a lower eNOS expression in sinusoidal endothelium. 35 These messages informed that elevated MAP could reduce ICP by the functional and structural alteration in vessels as well as in the cavernous spaces of the erectile tissue.…”
Section: Discussionmentioning
confidence: 99%
“…After treatment with ICA, the ICP max /MAP significantly improved, which is consistent with the previous experiments. [4][5][6] A large number of studies have shown that EMP and EPC are closely related to arterial ED. 14,15,17 In this study, we further investigated the effect of ICA on EMP, EPC, and platelets in SHR and its relationship with erectile function by FCM.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] These results indicated that ICA could improve the erectile function of SHR by up-regulating the eNOS /nitric oxide (NO)/cyclic guanosine monophosphate (cGMP) signaling pathway and inhibiting the RhoA/Rho kinase signaling pathway in the corpus cavernosum tissue of SHR. [4][5][6] Other studies have also found that ICA can increase the expression of eNOS, nNOS, and inducible NO synthase (iNOS)…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation